First report of Wautersiella falsenii genomovar 2 isolated from the respiratory tract of an immunosuppressed man. (2016) - Giordano, Cesira; Falleni, Margherita; Capria, Anna-Lisa; Caracciolo, Francesco; Petrini, Mario; Barnini, Simona
Abstract: Wautersiella falsenii is a Gram-negative, non-motile rod, which grows aerobically on common isolation media and is the only acknowledged species among the genus Wautersiella. Two genomovars, namely 1 and 2, phenotypically indistinguishable but genotypically different, are described. To date, few case reports detailing the clinical disease associated with W. falsenii have been reported, all describing localized infection. To our knowledge, this study reports the first isolation of W. falsenii genomovar 2 from a respiratory sample of an immunosuppressed man. Our hypothesis is that the patient was harboring W. falsenii genomovar 2 and both the immunosuppression and the antimicrobial treatments provided a chance for this organism to emerge. The clinical significance of this result is yet to be evaluated. Although infection with W. falsenii remains rare, this bacterium should not be underestimated mainly because of its natural resistance to many available antimicrobials.